Parametric bionic hand-inspired optimization of femoral condylar prosthesis attachment surfaces - Wang, Lin; Zhou, Wen; Sun, Hui; Lian, Shuqi (Frontiers in Bioengineering and Biotechnology, 2025)
Traditional femoral condylar prosthesis attachment surfaces often lack adequate anatomical conformity, resulting in clinical complications such as prosthesis loosening and stress shielding. Inspired by the multi-level curvature adaptation observed in the palmar-phalangeal hierarchy, this study introduces a novel bionic hand-inspired design methodology to enhance the adaptability of prosthesis attachment surfaces. Unlike conventional biomimetic approaches that primarily focus on replicating macroscopic shapes, our method transforms the functional hierarchy of phalange-palm interactions into a parametric design system, enabling dynamic curvature control to improve the fit of the prosthesis to the condylar resection surface. The proposed framework encompasses: (1) constructing bionic finger contour feature lines based on critical anatomical landmarks, (2) parameterizing the bionic fitting surface through bending and dimensional parameters, and (3) projecting this surface onto the femoral condyle to generate the attachment surface. Experimental validation across parametric variations (n = 4 groups) confirmed that the optimized bionic structure offers superior editability, anatomical adaptability, and a significantly improved fit, as evidenced by a Hausdorff distance of 0.29 mm. This approach simplifies the design process compared to conventional CAD-based methods while providing clinically adaptable parameters. The methodology demonstrates potential for application to a broader range of orthopedic implant designs where anatomical conformity is critical.